Being there: The role of place in children's picturebooks. (1st March 2012) - Manolessou, Katherina; Salisbury, Martin
The depiction of place and environment can play a key role in predominately visual texts such as children's picturebooks, sometimes taking on the status of a character in its own right. Representations of place, literal or implicit, provide the stage or backdrop on or before which the actors perform. The article examines this often unnoticed element of pictorial sequential design and its role in anchoring and propelling visual narrative. The article draws on Katherina Manolessou's practice-based Ph.D. research and Professor Martin Salisbury's experience as her supervisor, along with Professor Morag Styles of the University of Cambridge. The article identifies a range of approaches to scene-setting and explores different cultural traditions and approaches to the representation of space and environment, pictorial, schematic and implied. The focus of this article is primarily on process, on the making of a picturebook as distinct from being an analysis of the finished product.